Impact of commodity prices on exchange rates in commodity-exporting countries - Jiménez Rodríguez, Rebeca; Morales-Zumaquero, María Amalia (Wiley, 2020)
This paper studies the link between real exchange rates and commodity prices, over the period 1993M1–2018M12, for commodity-exporting countries by analysing countries individually and considering the possibility of structural breaks. Our results suggest that: (a) the movements in the price of the main commodity (i.e., the one whose share is at least 20% of total commodity export) affect significantly to the real exchange rate; (b) the sign of the effect of commodity prices on real exchange rate is not clearly positive (as was found by earlier analyses using panel data), but it depends on the country considered; and (c) the negative effects of the possession of natural resources observed in the past decades seem not to be now overwhelming.
Keywords: Macroeconomía; Precios; Tipos de cambio; Commodity prices; Real effective exchange rate; Structural breaks